Optimisation of ultrasound-assisted extraction of ethyl p-methoxycinnamate from Kaemperia galanga L. rhizomes - Do Thi Dinh; Ngo Thi Phuong; Ta Thi Thao; Pham Thi Nhung; Nguyen Thai An; Le Minh Ha (Vietnam Journal of Science, Technology and Engineering)
Ultrasound-assisted extraction has become a prevalent technique for isolating various natural bioactive compounds. This study examines the influence of ultrasonic power, extraction temperature, and extraction time on the yield of ethyl p-methoxycinnamate (EPMC) from Kaemperia galanga rhizomes. The content of EPMC in the residue and the purity of the isolated EPMC were quantified using the gas chromatography - mass spectrometry (GC/MS) method. Response surface methodology (RSM) identified the optimal extraction conditions as follows: ultrasonic power of 100 W, extraction temperature of 56°C, and extraction time of 34 minutes. Under these conditions, the maximum EPMC extraction efficiency was 2.93%. Subsequently, ultrasound-assisted extraction at these conditions, combined with recrystallisation, was employed to isolate EPMC with a high purity exceeding 95% and an isolation efficiency of approximately 2.53% relative to the dried raw material. The purification efficiency of EPMC from the extract was approximately 82.9%. The isolation procedure proved to be stable and reproducible, marking the first report on the ultrasound-assisted extraction of EPMC from Kaemperia galanga rhizomes.